2017
DOI: 10.5430/jha.v6n3p26
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence among emergency medical services workers in Riyadh, Saudi Arabia

Abstract: Background: Globally, workplace violence toward health care providers is an area of concern. The impact of workplace violence on health care providers is significant. Objectives: The study was conducted to evaluate the prevalence of workplace violence (physical and verbal) among emergency medical services (EMS) workers in Riyadh. Methods: The study used a cross-sectional design that employed a self-administered confidential questionnaire, which was distributed to all emergency medical personnel. A well-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 14 publications
9
41
0
1
Order By: Relevance
“…One of the findings of the study revealed non‐reaction to workplace violence as one of the common strategies used by the nurses participating in the study. The non‐reaction to workplace violence among pre‐hospital staff is not a new issue, and some studies in the Middle East such as Saudi Arabia (EMTs) (Alharthy et al, ) and Iran (EMTs) (Hosseinikia, Zarei, Najafi Kalyani, & Tahamtan, ) confirm this finding. What is important in this study is that the reasons for the non‐reaction to workplace violence were uncovered, which included fears of a deteriorating incident scene, harming the patient and ineffective follow‐up of workplace violence.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…One of the findings of the study revealed non‐reaction to workplace violence as one of the common strategies used by the nurses participating in the study. The non‐reaction to workplace violence among pre‐hospital staff is not a new issue, and some studies in the Middle East such as Saudi Arabia (EMTs) (Alharthy et al, ) and Iran (EMTs) (Hosseinikia, Zarei, Najafi Kalyani, & Tahamtan, ) confirm this finding. What is important in this study is that the reasons for the non‐reaction to workplace violence were uncovered, which included fears of a deteriorating incident scene, harming the patient and ineffective follow‐up of workplace violence.…”
Section: Discussionmentioning
confidence: 90%
“…The main reasons for the high prevalence of workplace violence in the pre‐hospital setting include critical workplace conditions, working in unpredictable environments (Bigham et al, ; Gormley et al, ), unexpected deaths, driving accidents and severe injuries (King, ; Lindström, Bohm, & Kurland, ). In this regard, studies have reported the annual rate of all types of workplace violence experienced by EMTs as follows: 65% in Saudi Arabia (Alharthy et al, ); 75% in Iran (Rahmani et al, ); 67% in Turkey (Deniz, Saygun, Eroğlu, Ülger, & Azapoğlu, ); 66% in Sweden (Petzäll et al, ); 83% in India (Dhar et al, ); 88% in Australia (Boyle, Koritsas, Coles, & Stanley, ); and 75% in Canada (Bigham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a Turkish study, the risk of violence was 2.4 times higher among HCWs aged less than 30 years than older ones; however, the experience duration was not a significant risk factor for violence [14]. In Riyadh, KSA, two studies showed that less experienced and younger HCWs respondents were more likely to encounter violent attacks than their counterparts [5,10]. Unexpectedly, the present study showed that older HCWs aged 50 years or more were 6 times more likely to experience violence than younger HCWs aged less than 30 years (P < 0.0001, OR � 6.24, 95% CI: 2.43-15.9).…”
Section: Discussionmentioning
confidence: 96%
“…e most frequent type of violence was verbal abuse. e aggressor can be the patient, patient's relatives, or coworker [5]. In another study in Riyadh, almost half of the nurses had been attacked, and the majority of participants perceived violence as verbal abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Ambulans çalışanları yüksek oranda şiddete maruz kalmaktadır. [29][30][31] Fiziksel ve sözel şiddete maruz kalan acil yardım merkezi çalışanlarının, herhangi bir saldırganlığa maruz kalmamış olanlara kıyasla anksiyete oranlarının anlamlı olarak daha yüksek olduğu bulunmuştur. 32 Yapılan bir çalışmada Acil hizmeti sunanların %68'nin kişisel güvenliklerinden korktuğunu bildirmektedir.…”
Section: Introductionunclassified